BENEFITS AND CHALLENGES OF USING AUTHENTIC TEXTS, AUDIO, AND VIDEO MATERIALS TO ENHANCE THE STUDENT’S MOTIVATION IN TRANSLATION (KONFERENSIYA, 2025)
This study explores the benefits and challenges of integrating authentictexts, audio, and video materials into practical translation as a means of enhancinglanguage learning. Authentic resources expose learners to real-world linguisticpatterns, idiomatic usage, and diverse registers, thereby enriching their linguisticcompetence. They also foster intercultural awareness, pragmatic understanding, andprofessional readiness by simulating real translation contexts. Moreover, theinclusion of audio-visual materials promotes multimodal skills such as subtitling anddubbing, aligning with the demands of the modern translation market